A new species of Lessertia (Galegeae, Leguminosae) from Gauteng Province, South Africa - van Wyk, Ben-Erik; Nkonki, Tandiwe; van Wyk, Teodor (Phytotaxa, 2016)
A new species of Lessertia, L. uniflora, is described. It is morphologically similar to L. mossii but differs in the decumbent habit, slender stems, longer leaves, shorter, thinner peduncles and especially in the almost invariably single-flowered inflorescences, the smaller flowers, glabrous style, larger winged fruits and more numerous seeds. It appears to be a rare species and is known from only one small population in the Marievale Bird Sanctuary southeast of Johannesburg in Gauteng Province, South Africa.